View from Speyside, Tobago - (:unkn) unknown (Printed in England, 2011)
Description printed on the back of the postcard: "This view is typical of the coastal scenery of Tobago and shows Goat Island and Little Tobago an attempt is being made to acclimatize Birds of Paradise."
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Capes (Coasts); Bays